Uma educação imperfeita para uma liberdade imperfeita : escravidão e educação no Espírito Santo (1869-1889) - França, Aldaíres Souto (2006)
This study aimed to investigate the education, official measures or not, regarding the enslaved workers who are black, free or freed during the last decades of the century XIX, from the thought of the ruling-intellectual elite “espírito-santense” expressed principally in the local press; as well as to understand the means of appropriation of these education practices for these historical subjects. The research was based on the field of the History of the Education with the proposal of boarding anchored in Cultural History. The investigation was based on printed fountains, specifically the Espírito Santo´s press, and on the crossroad with other documentary corresponding fountains of that period, such as: provincial laws, regulations, presidents' reports of the Province, newspapers of other provinces and of the Court, and Annals of the Legislative Assemblies, available in the State Archive of the Espírito Santo (APEES), in the Archive of the Curia Diocesana and in the Archive of the Legislative Assembly. Besides, they were thought other bibliographical specific fountains on the Province of the Espírito Santo in this period, like, for example, Basílio Carvalho Daemon (1879), Amâncio Pereira (1914), Maria Stela de Novaes (1963 and 1964), Primitive Moacyr (1940), Serafim Derenzi (1965) and José Teixeira Oliveira (1975). The reports and Jean-Baptiste's images (1978), the photographies of George Ermakoff (2004) and the reports of Saint-Hilaire (1974) were also of great importance for our research. So, it was possible to conclude that the education offered to the black enslaved, free and freed workers was imperfect like the freedom offered and conquered by these, since it privileged the preoccupation of the ruling-intellectual elite with the “education for the work ” and in the imposition of a model of integration, aiming to maintain the hierarchy so much racial like the social one